2020
DOI: 10.1021/acsanm.9b02187
|View full text |Cite
|
Sign up to set email alerts
|

Side-Chain-Dependent Binding of bis-Naphthalimide Self-Assembled Nanoparticles to G-Quadruplex DNA for Potential Anticancer Therapy

Abstract: Novel bis-naphthalimide (NI)-based molecules composed of space linkers of phenyl dialkyne (bis-NI1 and bis-NI2), triazole (bis-NI3 and bis-NI4), and alkyne (bis-NI5 and bis-NI6) with the distinctive side chain of 2,6-diisopropylaniline or 2,4,6-trimethylaniline were designed and synthesized as nanoparticles (NPs) that bind to Gquadruplex (G4) DNA. The supramolecular assemblies of the bis-NIs were found to form isolated spheres (bis-NI1, bis-NI3), dumbbells with or without a cylindrical bridge (bis-NI2, bis-NI4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…They reported that SALs made from 8-aryl-2′deoxyguanosine derivatives can form precise hydrophilic supramolecular G-quadruplexes (SGQs) with excellent size, shape, and charge complementarity to G-quadruplex DNA [13]. Another research revealed bis-NI1, bis-NI4, and bis-NI6 as possible anticancer therapeutic candidates to target G-quadruplexes on the DNA [14]. The targeting approach for the G-quadruplexes at the specific regions of the genome often is aimed at stabilization of their structure.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that SALs made from 8-aryl-2′deoxyguanosine derivatives can form precise hydrophilic supramolecular G-quadruplexes (SGQs) with excellent size, shape, and charge complementarity to G-quadruplex DNA [13]. Another research revealed bis-NI1, bis-NI4, and bis-NI6 as possible anticancer therapeutic candidates to target G-quadruplexes on the DNA [14]. The targeting approach for the G-quadruplexes at the specific regions of the genome often is aimed at stabilization of their structure.…”
Section: Introductionmentioning
confidence: 99%